2017
DOI: 10.1177/0038040717694876
|View full text |Cite
|
Sign up to set email alerts
|

Girls Behaving Badly? Race, Gender, and Subjective Evaluation in the Discipline of African American Girls

Abstract: School disciplinary processes are an important mechanism of inequality in education. Most prior research in this area focuses on the significantly higher rates of punishment among African American boys, but in this article, we turn our attention to the discipline of African American girls. Using advanced multilevel models and a longitudinal data set of detailed school discipline records, we analyze interactions between race and gender on office referrals. The results show troubling and significant disparities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 30 publications
(28 reference statements)
2
161
0
Order By: Relevance
“…This also includes taking into consideration other social organizing factors (e.g., gender), influence social construction via criminalization and medicalization. Results suggest that girls are significantly less likely than boys to experience punishment or therapy/medication, but that the punishment rates of black girls may be similar to those of white boys (Morris and Perry ). Similarly, while diagnoses for behavior disorders such as ADHD are increasing for girls, boys are more likely to use therapy or medication than girls (Hinshaw and Scheffler ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This also includes taking into consideration other social organizing factors (e.g., gender), influence social construction via criminalization and medicalization. Results suggest that girls are significantly less likely than boys to experience punishment or therapy/medication, but that the punishment rates of black girls may be similar to those of white boys (Morris and Perry ). Similarly, while diagnoses for behavior disorders such as ADHD are increasing for girls, boys are more likely to use therapy or medication than girls (Hinshaw and Scheffler ).…”
Section: Discussionmentioning
confidence: 85%
“…), I include a time‐invariant measure of mother's age at delivery . Because boys are more likely to be punished or medicalized than girls (Morris and Perry ), I control for gender (1 = girl).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, 2.6 million children and adolescents are temporarily removed from school as a result of out‐of‐school suspension and 2.7 million are excluded from class as a result of in‐school suspension (Office of Civil Rights, ). Reform efforts have led to recent declines in some states (Loveless, ), but overall rates are still high, particularly for disadvantaged and racial minority students, not because juvenile crime rates are high but because suspension is often in response to minor misbehavior like classroom disruptions and attendance problems (Kupchik, ; Morris & Perry, ; Skiba et al., ). This is problematic because in a growing body of research, scholars have suggested that suspension may be harmful for child and adolescent development (Cuellar & Markowitz, ; Jacobsen, Pace, & Ramirez, ; Mittleman, ; Morris & Perry, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to examine how the intersections of race and gender influence the disciplinary experiences of Black females, as the behavioral standards on which Black female students are evaluated may be based in part on their compliance with gender norms (Collins, 2004). Morris and Perry (2017) propose that school discipline penalizes African American girls for behaviors perceived to transgress normative values of femininity. Costenbader and Markson (1998) noted that although most students suspended from school self-reported physical aggression as the main reason for their suspensions, female students were more likely to self-report minor behavioral infractions such as gum chewing, failure to comply with a prior disciplinary sanction, and defiance as reasons for their suspensions.…”
Section: Black Girls and School Disciplinementioning
confidence: 99%